PENGARUH PENGGUNAAN MEDIA WORDWALL TERHADAP HASIL BELAJAR BAHASA INDONESIA MATERI MENGENAL PERASAAN PADA SISWA KELAS II SDN GAJAHMUNGKUR 04 SEMARANG - Thessa Dyah Kusumaningrum; Haryadi; Bernadus Wahyudi Joko Santoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using Wordwall media on Indonesian language learning outcomes in the topic of recognizing emotions among second-grade students at SDN Gajahmungkur 04 Semarang. This research employed a quantitative approach using a quasi-experimental method with a One Group Pretest-Posttest Design. The subjects consisted of 25 students in the 2025/2026 academic year. The research instrument was a learning achievement test focusing on students’ ability to understand emotional vocabulary and express it in simple sentences. Data were collected through pretest and posttest, then analyzed using a paired sample t-test with SPSS 26. The results indicated a significant improvement in students’ learning outcomes after using Wordwall, with the average pretest score of 56.60 and posttest score of 82.40. The sig. (2-tailed) value of 0.000 < 0.05 shows that the use of Wordwall media had a positive effect on students’ Indonesian language learning outcomes. Wordwall effectively enhanced students’ conceptual understanding, motivation, and engagement during learning activities. Therefore, Wordwall can be used as an effective interactive learning medium suitable for elementary students, especially in teaching emotional topics such as recognizing feelings.